Interdisciplinary Integration in the Learning Process of Students in Humanities - Shachkova, Elvira V. (International Journal of Psychosocial Rehabilitation, 2020)
The paper analyzes the process of interdisciplinary integration, learner-centered and interactive approach in teaching future teachers in humanities.The aim of the work is to analyze the subject matter of synthesis and the process of integration, which consists of creative forces: artistic intuition and intellect of future humanitarians. The methods and results justify the importance of interdisciplinary integration in the learning process of students in humanities, which is considered leaning on individual and interactive approaches.The essence of teacher's professional individuality lies in an efficient self-consciousness that includes a reasonable position of personality, internal system of abilities, harmony and integrity, continuous self-development and formation of a personality, acquisition of competencies and self-assertion, self-actualization and realization of individual value in personal and social factors.In education, the professional individuality is described as a progressive phenomenon, multilevel system, or a personal life agenda. The subject matter of the interconnection between intuition and intellect in the scientific cognition of the existing reality is revealed. The authors also describe the methods promoting activation of creative activity are given.